PENGELOLAAN FASILITAS OBYEK WISATA PASIR TIKU DI KABUPATEN AGAM - Khairat, Iramatul (journal of residu, 2019)
This study aims to improve the management of existing facilities on the sea sand beach in terms of variable management of indicator facilities: places to eat and drink, places to shop, public facilities at tourist locations. This type of research is qualitative descriptive research. The research variable is facility management. The technique of collecting data uses the method of interview, observation and documentation, the selection of informants using purpose sampling techniques. The source of data in this study is the manager of Tiku beach attractions, namely the district tourism office and the community. The data obtained were analyzed using the data analysis techniques model Miles and Huberman by doing three results, namely; data reduction, data presentation and conclusion. The results of the study showed that in general, management in the coastal sand tourism object still could not be approved because the management was still not completed for the government which needed the community to manage it themselves did not need to be as expected. Inadequate number of visitors The number of visitors coming from outside the area. Facilities at sand beach resorts are not well managed because the number of people or visitors destroys the facilities provided and reduces community participation in making and maintaining existing facilities. It is suitable for tiku sand beach tourism which is a tourist attraction that is much in demand by outside tourists.